Ekonomi Pendidikan Di Era Digital: Tantangan Dan Peluang - Inviolata Rogo; Nuraini Asriati (Institut Penelitian dan Pengembangan Mandalika (IP2MI), 2024)
The digital era is closely related to technological tools. The existence of technology is currently considered very important in human life as a suxpport in carrying out various activities both in carrying out work and in terms of education. This article aims to describe the economic challenges and opportunities of education in the digital era. The method used is a qualitative method with a scoping review type. The research data used is secondary data in the form of accredited journals during the 2014-2024 period. The keywords used in this research are Education Economy, Digital, Challenges, Opportunities. From the 10 articles analyzed, it can be seen that there are various challenges and opportunities for the education economy in the digital era. Challenges such as technological accessibility and digital reach cannot be avoided in the current digital era, limited technological accessibility, digital inequality, Digital Security and Privacy. Apart from the challenges, there are also opportunities that can be exploited in the education economy in this digital era, such as the use of technology in learning, both in terms of providing information, apart from that, financial institutions can be implemented optimally, the use of websites and applications to carry out transactions and reporting will be more effective. and efficient. Can save operational costs so that they can be diverted to developing more modern facilities and infrastructure